MISTISISME YOGA : POLARISASI GERAKAN SPIRITUALITAS DALAM MASYARAKAT LINTAS AGAMA - Sugata, I Made (PANGKAJA, 2012)
Mysticism is understood as one of the practice of esoteric (secret) that aims to awaken the divine nature within oneself through yoga exercises. Yoga practices include moral training, physical training, mental training and spiritual training. When the yoga mysticism is a requirement by the public, there will be a polarization of spirituality movement regardless of his religion. Religion is a quest of mankind to God. Throughout the ages, mankind has always struggled in his quest for the secret and essence behind this life, and religion is a means or a connecting road and provides solutions to solve these problems.Spiritual journey undertaken by many people in order to search for meaning in a very individualistic modern life in a capitalist industrial society, as well as the rapid global developments affecting human life to fill in the blanks themselves. Thus, the approach described spirituality yoga mysticism in religious experience, mysticism polarization form of yoga in the movement of spirituality and mysticism influence of yoga in the interfaith community. Keywords: Mysticism, polarization, religion and spiritual